The short-term impact of government budgets on prices: evidence from macroeconomic models - Jérôme Henry; Pablo Hernández de Cos; Sandro Momigliano (European Central Bank (ECB), 2004)
This paper reviews the existing empirical evidence on the short-term impact on prices of fiscal variables and assesses it against new results from harmonised simulations, conducted with six well-established econometric models used by the ECB and five national central banks (NCBs) of the Eurosystem. The outcome is also compared with results from the European Commission and the OECD models. Overall, a broad consensus appears on the impact on prices of changes in individual government budget items in the euro area. In all cases, changes in government demand and in direct taxes paid by households have a limited impact on prices in the first year while, in contrast, changes in indirect taxes and employers' social security contributions have a relatively large impact. The second year results show that the effects on prices usually take some time to materialise fully; in particular, they often become large for the public consumption shock.
Keywords: E17; E31; E62; 330; euro area; Fiscal Policy; model simulations; prices